KAJIAN METODE BIOFILTRASI MENGGUNAKAN MEDIA SPUIT BEKAS PAKAI ( Alat Suntik Tanpa Jarum ) UNTUK MENURUNKAN KADAR BOD DAN COD PADA AIR LIMBAH LAUNDRY RUMAH SAKIT DR. SOEDARSO PONTIANAK TAHUN 2015 - Risa, Tia Tio; Pradana, Tedy Dian; Asmadi, Asmadi (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2016)
Hospital wastewater derived from the laundry activities contains chemical compounds and pathogenic microorganisms that cause not only diseases to the surrounding community but also pollution. These effects increase the Biologycal Oxygent Demand (BOD) and the Chemical Oxygent Demand (COD) that lead foul-smelling and black-colored surface of the water. However, used syringe biofiltration can be employed to process this waste. This study aimed at testing the used syringe-biofiltration in reducing the BOD and COD levels in laundry waste at Dr. Soedarso hospital Pontianak. A quasi-experimental design with one group pretest posttest was carried out in this study. Laboratory test result showed that the average BOD level before processing was 103.63 mg/l and after processing into 46.41 mg/l, with an efficiency of 55.21 %. In addition, the average COD level before processing was 413.70 mg/l, and processing was 195.88 mg/l with an efficiency of 45.92 %. This study suggests the management of the hospital to pay more attention on the pH value and the use of blower in using used syringe biofiltration method and to consider used syringe biofiltration method to process wastewater.Keywords : Laundry waste, biofilter, used syringe, BOD, COD